EVALUASI DANA ALOKASI KHUSUS (DAK) BIDANG PENDIDIKAN DI KABUPATEN CILACAP TAHUN 2013 - Susanti, Foni; Subowo, Ari; Rengga, Aloysius (Journal of Public Policy and Management Review, 2015)
At the Budget Year 2013, the Province of Central Java gets budget allocation (DAK) as many of Rp 2.229.164.420.000,- that allocated for 35 district / cities and Provincial Governments of Central Java. District Cilacap is the largest receiver of DAK between 35 district / cities in the province of Central Java as many of Rp. 108.157.350. The result of DAK activities on the field of education in District Cilacap 2013 consist of primary education (Elementary School and Secondary School) and secondary education (High School and Vocational High School). Both of them are regulated by the decision of Regent of District Cilacap number 425 / 428 / 14 / 2013 about the Establishment of Educational Institutions of the Recipient of Special Allocation Funds on the Field of Education in Budget Year 2013 at Department of Education, Youth and Sport District Cilacap.The activities of Special Allocation Funds (DAK) on the field of primary education have given the maximum result as expected. Inhibit factor of activities enforcement of DAK on primary education is related to financial policy, it isnâ€™t technical factor in beneficiary school. Because it is related to another policy, it canâ€™t be said as a problem on DAK activity implementation. The aim of DAK activities on the field of primary education is implemented. The efforts such as input, process, and output indicator are good. The graduation rates are considerably higher and not passing rates are lower.DAK activities on the field of secondary education still not entirely provide expected result. There are inhibit factors on the activity implementation of DAK in secondary education. The aim of DAK activities on secondary education has not maximum implemented. The realization by 50%. It can be seen on input, process, and output of Department of Education and beneficiary school efforts are good. It is profoundly that the graduation rates are 100% or almost 100%. The expected impacts was comparable with the efforts.Â